COMBINED COUNTERSINK-TAP TOOL FOR THE PROCESSING OF PARTS OF SHIP MACHINES, MECHANISMS AND FITTINGS: DESIGN AND CALCULATIONS - N. M. Vagabov; A. Z. Kurbanov; M. A. Magomedovа (Вестник Дагестанского государственного технического университета: Технические науки, 2018)
Objectives The aim of the study is to revise design and calculation methods for metal cutting tools due to an increase in their quality requirements. The design of metal cutting tools necessitatesfinding a solutionto a number of issues related to their calculation, construction, manufacture and operation. However, the methods for solving these issues have always been dependent on the means that the toolmaker had at his disposal.Methods Contemporary electronic computers and digital equipment offersignificant opportunities for improving the process of machine tool design. To solve this problem, it is necessary to generate calculation methods that aresufficiently analytical to becapable of rigorously formalising the entire designing process. They have to support clearly defined optimisation criteria and be of sufficient generalityto enable all problems associated with tool designto be solved in a complex manner. That is, these calculation approaches have to support methodologies for solving the problems of the surface shaping by tools, calculating the cutting schemes, as well as the strength and manufacturability of the cutting part.Results A flowchart of a calculation algorithm for designing and calculating the combined countersink-tap toolhas been developed, allowing the process of calculating its basic parameters to be automated according to a predefined programme. Conclusion The developed flowchart of the calculation algorithm with the preset programme allows the process of calculating the basic parameters of the combined countersink-tap tools, used for threading in the parts of ship machines, mechanisms and ship fittings from hard-to-process materials, to be automated. The flowchart can similarly be used to automate the process of calculating the parameters of any cutting tools used to process any materials.